Copper-catalyzed remote C-H monofluoromethylation of 8-aminoquinolines with dimethyl phosphonate as reductant. Issue 40 (3rd October 2019) - Han, Shuaijun; Wu, Qingsong; Mele, Lucas; Ding, Licheng; Li, Jingya; Zou, Dapeng; Wu, Yusheng; Wu, Yangjie
Graphical abstract: Highlights: A new approach to C5 ethoxycarbonylmonofluoromethylation of quinolines. Copper-catalyzed system was applied. This catalytic system features high-efficiency and synthetic convenience. The reaction proceeds under air. Abstract: A simple and efficient copper-catalyzed monofluoromethylation of 8-aminoquinolines with 2-bromo-2-fluoroacetate has been described with HPO(OMe)2 (dimethyl phosphonate) as reductant. The reaction tolerates a variety of quinoline amides and monofluoroalkyl bromides. Significant advantages of this protocol include synthetic convenience and high reaction efficiency.